A Case Study of Midlatitude Noctilucent Clouds and Its Relationship to the Secondary‐Generation Gravity Waves Over Tropopause Inversion Layer. Issue 17 (1st September 2022) - Miao, Jiaxuan; Gao, Haiyang; Kou, Leilei; Zhang, Yehui; Li, Yan; Chu, Zhigang; Bu, Lingbing; Wang, Zhen
Abstract: A sporadic case of noctilucent clouds (NLCs) was observed unexpectedly on the night of the 6–7 July 2020 in Beijing (40°2′N, 115°30′E). The noticeable wavy structures and observed ambient temperature (135.54K at the mesosphere and lower thermosphere [MLT]), both indicated that the increase in temperature oscillations could be the cold phase of gravity waves (GWs). The reasons for NLC formation were analyzed based on the observations and model data sets in our study. The real‐time synoptic analysis revealed that there were GWs originally generated by a squall line in the troposphere. Due to the blocked effect of a stable tropopause inversion layer (TIL), the GWs broke, leading to strong energy dissipation near the TIL. The reverse ray tracing analysis between the TIL and NLCs' layer revealed the travel distance (206.88 km) and time (49.91 min) of GWs. These findings show that the turbulence over the TIL (at approximately 14.64 km) excited secondary GWs, which propagated upwards toward the mesosphere and probably interacted with diurnal and semi‐diurnal tides. The cold phase of the larger‐amplitude waves can provide optimal conditions for NLCs forming. Our study highlights the significance of dynamic coupling mechanisms regarding the effects from troposphere to MLT thermal conditions and offers a case study for the increasing occurrences of NLCs at midlatitudes. Plain Language Summary: Noctilucent clouds (NLCs) are ice clouds forming at 80–86 km during summertime in the Northern Hemisphere. During the night of 6–7 July 2020, a Chinese photographer captured the occurrence of NLCs in Beijing (40°2′N, 115°30′E). The wavy structures in the photographs revealed that the occurrence of NLCs had a close relation with the atmospheric gravity waves (GWs), the significant transport of momentum and energy in the atmosphere. We used comprehensive data sets and models to locate the source of these GWs. The real‐time synoptic analysis in the troposphere revealed that the GWs were generated by a convective system, a squall line. However, a stable tropopause inversion layer inhibited the waves like a huge lid, resulting in strong energy dissipation and exciting new GWs propagating upwards. The secondary‐generation GWs can interact with large‐scale waves and cause severe cooling in the MLT, providing an ideal condition for the growth of ice particles in NLCs. These particles integrated the wave source at the tropopause and GWs that are visible in the NLCs for the first time at midlatitudes. The results inspired us to further explore the connection between the troposphere and the upper atmosphere in the future studies. Key Points: The mechanism of a sporadic case of formation of midlatitude noctilucent clouds (NLCs) in China is demonstrated The interaction between gravity waves (GWs) and tidal waves substantially cooled the NLC layer Turbulence of the tropopause inversion layer excited secondary GWs which propagated upwards toward the mesosphere